Anti-colorectal cancer effect of total minor ginsenosides produced by lactobacilli transformation of major ginsenosides by inducing apoptosis and regulating gut microbiota - Yunjiao Shen; Yunjiao Shen; Yansong Gao; Ge Yang; Zijian Zhao; Yujuan Zhao; Lei Gao; Shengyu Li (Frontiers in Pharmacology)
ObjectiveMinor ginsenosides have demonstrated promising anticancer effects in previous reports. Total minor ginsenosides (TMG) were obtained through the fermentation of major ginsenosides with Lactiplantibacillus plantarum, and potential anticancer effects of TMGs on the mouse colon cancer cell line CT26.WT, in vitro and in vivo, were investigated.Materials and MethodsWe employed the Cell Counting Kit-8 (CCK-8), TdT-mediated dUTP nick end labeling (TUNEL), and Western blot analysis in vitro to explore the anti-proliferative and pro-apoptotic functions of TMG in CT26.WT cells. In vivo, a xenograft model was established by subcutaneously injecting mice with CT26.WT cells and administering a dose of 100 mg/kg/day TMG to the tumor-bearing mice. The level of apoptosis and expression of various proteins in the tumor tissues were detected by immunohistochemistry and Western blot. High-throughput 16S rRNA sequencing was used to determine the alterations in the gut microbiota.ResultsIn vitro studies demonstrated that TMG significantly inhibited proliferation and promoted apoptosis in CT26.WT cells. Interestingly, TMG induced apoptosis in CT26.WT cells by affecting the Bax/Bcl-2/caspase-3 pathway. Furthermore, the result of the transplanted tumor model indicated that TMG substantially enhanced the activities of Bax and caspase-3, reduced the activity of Bcl-2, and suppressed the expression of Raf/MEK/ERK protein levels. Fecal analysis revealed that TMG reconstructed the gut microbiota in colorectal cancer-affected mice by augmenting the abundance of the advantageous bacterium Lactobacillus and decreasing the abundance of the harmful bacterium Proteus.ConclusionTMG can exhibit potent anti-colorectal cancer effects through diverse apoptotic mechanisms, with their mode of action closely related to the regulation of gut microbiota.